Recommendations for teaching Physical Education in schools during the Covid-19 pandemic: a review protocol (Research, Society and Development, 2021)
The aim of this research is to accomplish a protocol of review in order to map out evidences about the recommendations for Physical Education teaching in schools, during the Covid-19 pandemic in Brazil. It is about a protocol of research based on Joanna Briggs Institute (JBI) manual recommendations, following the Preferred Reporting Items for Systematic and Meta-Analyses - Extension for Scoping Reviews (PRISMA-ScR) checklist. It will be achieved the search and data gathering in the month of October/2021 with the Science of Health (DeCS) descriptors and Medical Subject Headings (MeSH). The selection of the studies will be done by two researchers, independently of each other. For a better interpretation of results, it will be used the software IRaMuTeQ, followed by similarity analysis and cloud of words as well as text body based on thematic analysis.